(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Over the years, numerous studies have explored the impact of nutrition education on children’s behaviour and attitudes, consistently demonstrating its positive influence on nutritional habits, physical well-being, and academic performance. This study aims to investigate the effects of a nutrition education program on students’ attitudes and behaviors concerning nutrition, sports, and academic achievement. Employing an experimental research design with pretest-post-test control groups, the study engaged 60 students from Kazakhstan. Data collection involved the utilization of scales assessing nutritional behaviour, attitudes towards nutrition, sports performance, attitudes towards sports, along with a general academic achievement test. Results reveal that students exposed to the nutrition education program exhibited enhanced nutrition attitudes and behaviors, coupled with elevated sports performance and attitudes compared to their counterparts in the control group. Nevertheless, no notable disparity emerged in overall academic achievement between the experimental and control groups. These findings underscore the pivotal role of nutrition education interventions in cultivating healthier lifestyles among schoolchildren, with potential implications for comprehensive educational strategies aimed at fostering holistic well-being and academic success. The study highlights the importance of integrating nutrition education into school curriculum to promote healthier lifestyles and enhance overall academic achievement